2010
DOI: 10.1007/s00520-009-0796-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of malnourishment in the head and neck cancer patient: assessment tools and nutrition education of radiation oncologists

Abstract: Assessment or screening for malnourishment in the head and neck cancer patient should be a routine part of the initial consultation. Radiation oncologists and their medical team, including nutritionists, should use an appropriate nutrition screening and assessment tool in addition to the body weight as an indicator of malnourishment. Nutrition education provided to radiation oncologists should be improved to better communicate the positive effects of nutrition interventions on prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…These recommendations have been quite recently replicated in ad hoc ASPEN guidelines [14] and by the National Cancer Institute [15]. However, a recent survey in UK [16] showed that 80% of specialist oncological trainees expressed uncertainty or a lack of confidence in their ability to identify malnutrition and a similar study in US radiology oncologists [17] reported that only 9% of them used body weight plus other assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…These recommendations have been quite recently replicated in ad hoc ASPEN guidelines [14] and by the National Cancer Institute [15]. However, a recent survey in UK [16] showed that 80% of specialist oncological trainees expressed uncertainty or a lack of confidence in their ability to identify malnutrition and a similar study in US radiology oncologists [17] reported that only 9% of them used body weight plus other assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…This problem of underestimating the importance of proper nutritional assessment in cancer patients is prevalent in more developed nations too because of cumbersome and detailed nature of these nutrition assessment tools. [56]…”
Section: Introductionmentioning
confidence: 99%
“…There were also some barriers of nutrition support in practice. Based on the literature, economic factors [57], low adherence to guidelines [11,58], and behavior of medical staff [15][16][17] are the barriers of nutrition support. In this study, medical staff in Macao mentioned other barriers of nutrition support, including misunderstanding of the cancer patients and their families, lack of standard guidelines, over workload, and loss of appetite of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cancer patients at difference disease stages with different therapies meet different nutrition needs, and the starting point of nutrition support should be well considered. In addition, the cooperation, attitude, and knowledge of participants, such as physicians and nutritionists, involved in nutrition support among cancer patients, are some of the challenges of utilization of nutrition support [15][16][17].…”
Section: Introductionmentioning
confidence: 99%